2017
DOI: 10.1186/s12014-017-9143-3
|View full text |Cite
|
Sign up to set email alerts
|

OLFM4, KNG1 and Sec24C identified by proteomics and immunohistochemistry as potential markers of early colorectal cancer stages

Abstract: BackgroundDespite recent advances in colorectal cancer (CRC) diagnosis and population screening programs, the identification of patients with preneoplastic lesions or with early CRC stages remains challenging and is important for reducing CRC incidence and increasing patient’s survival. MethodsWe analysed 76 colorectal tissue samples originated from early CRC stages, normal or inflamed mucosa by label-free proteomics. The characterisation of three selected biomarker candidates was performed by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…20 The OLFM4 gene has been analyzed as a putative biomarker in many cancers, including gastrointestinal cancer, head and neck squamous cell carcinoma, cervical neoplasia, nonsmall cell lung cancer, triple-negative breast cancer and distant metastases in estrogen receptor-positive breast carcinoma. [20][21][22][23][24][25][26][27][28][29][30][31][32] In our study, we provide clinical evidence that reduced OLFM4 expression was associated with prostate cancer progression and with DNA methylation of CpG sites in the OLFM4 gene promoter region in human prostate adenocarcinoma. We also found that OLFM4 may play a role in regulating EMT, as well as tumor initiation and growth, in prostate cells.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…20 The OLFM4 gene has been analyzed as a putative biomarker in many cancers, including gastrointestinal cancer, head and neck squamous cell carcinoma, cervical neoplasia, nonsmall cell lung cancer, triple-negative breast cancer and distant metastases in estrogen receptor-positive breast carcinoma. [20][21][22][23][24][25][26][27][28][29][30][31][32] In our study, we provide clinical evidence that reduced OLFM4 expression was associated with prostate cancer progression and with DNA methylation of CpG sites in the OLFM4 gene promoter region in human prostate adenocarcinoma. We also found that OLFM4 may play a role in regulating EMT, as well as tumor initiation and growth, in prostate cells.…”
mentioning
confidence: 56%
“…In addition, DNA methylation of the OLFM4 gene has been found to be associated with tumor aggressiveness and patient outcomes in gastric carcinoma . The OLFM4 gene has been analyzed as a putative biomarker in many cancers, including gastrointestinal cancer, head and neck squamous cell carcinoma, cervical neoplasia, nonsmall cell lung cancer, triple‐negative breast cancer and distant metastases in estrogen receptor‐positive breast carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…Coupled with label-free shotgun proteomics and immunohistochemistry, these FFPE tissues have been widely used to identify biomarkers and drug targets in different disease settings [22], [23], [24], [25]. Several recent reports highlight a limited correlation between mRNA levels and corresponding protein levels, thus arguing in favor of proteomic approaches [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, tumor tissues would regulate the expression of proteins and promote the production of proteins associated with cancer progression. 7 Moreover, proteins were the functional effectors of cellular processes as well as the targets for a vast majority of therapeutics. 8 Therefore, the study of proteomics can improve our understanding of cancer aetiology and progression as well as heighten the assessment of cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%